The Discourse of Modernism - Reiss, Timothy J. (Cornell University Press, 1985)
Timothy J. Reiss perceives a new mode of discourse emerging in early seventeenth-century Europe; he believes that this form of thought, still our own, may itself soon be giving way. In The Discourse of Modernism, Reiss sets up a theoretical model to describe the process by which one dominant class of discourse is replaced by another. He seeks to demonstrate that each new mode does not constitute a radical break from the past but in fact develops directly from its predecessor.